2018
DOI: 10.1002/ldr.3201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rural landscapes in marginal areas of northern Spain: Past, present, and future

Abstract: European marginal areas hold multifunctional landscapes threatened by current changes in socio‐economy. Understanding both common and singular drivers behind the changes in the local socio‐economy and the landscapes is crucial to design sustainable policies at several spatial scales, which guarantee the provision of multiple ecosystem services in those areas. This work investigated the evolution of the local socio‐economy as well as the changes in landscape structure and composition in two areas (one in lowlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…Thus, for centuries, the Mediterranean mountains in Europe, especially those of mid‐altitude, were subjected to strong pressure from humans, who made use of natural resources for agrosilvopastoral activities (Lasanta et al, 2017; Sluiter & de Jong, 2007). Land use by humans expanded to its maximum between the mid‐19th and mid‐20th centuries, coinciding with greater demographic pressure (González Díaz, Celaya, Fernández‐García, Osoro, & García, 2019; Sancho‐Reinoso, 2013). Prolonged occupation by humans constructed cultural landscapes, featuring very diverse land uses in which grazing and agricultural land were the landscape matrix, whereas forest and shrubland covered a smaller area (De Aranzabal, Schmitz, Aguilera, & Pineda, 2008; García‐Ruiz & Lasanta, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for centuries, the Mediterranean mountains in Europe, especially those of mid‐altitude, were subjected to strong pressure from humans, who made use of natural resources for agrosilvopastoral activities (Lasanta et al, 2017; Sluiter & de Jong, 2007). Land use by humans expanded to its maximum between the mid‐19th and mid‐20th centuries, coinciding with greater demographic pressure (González Díaz, Celaya, Fernández‐García, Osoro, & García, 2019; Sancho‐Reinoso, 2013). Prolonged occupation by humans constructed cultural landscapes, featuring very diverse land uses in which grazing and agricultural land were the landscape matrix, whereas forest and shrubland covered a smaller area (De Aranzabal, Schmitz, Aguilera, & Pineda, 2008; García‐Ruiz & Lasanta, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for centuries, the Mediterranean mountains in Europe, especially those of midaltitude, were subjected to strong pressure from humans, who made use of natural resources for agrosilvopastoral activities (Lasanta et al, 2017;Sluiter & de Jong, 2007). Land use by humans expanded to its maximum between the mid-19th and mid-20th centuries, coinciding with greater demographic pressure (González Díaz, Celaya, Fernández-García, Osoro, & García, 2019;Sancho-Reinoso, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rural tourism aims to sustain rural architecture and landscapes, thereby promoting creative activities related to the natural and historical backgrounds of rural areas for the appropriate development of these rural landscapes and their cultural heritage. This is also a major pathway in the sustainable development of rural areas [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For this task, for accurate classification, researchers use high-resolution imagery (< 5m). Taking in consideration that highresolution imageries are not of open-source character, not many studies can be found in the literature on the particular topic [4,5].…”
Section: Introductionmentioning
confidence: 99%